Multiple Levels of Analysis From a Longitudinal Perspective: Some Implications for Theory Building - Dansereau, Fred; Yammarino, Francis J.; Kohles, Jeffrey C. (Academy of Management Review, 1999)
Fred Dansereau, Francis J. Yammarino, Jeffrey C. Kohles, Multiple Levels of Analysis from a Longitudinal Perspective: Some Implications for Theory Building, The Academy of Management Review, Vol. 24, No. 2 (Apr., 1999), pp. 346-357